Pengembangan Rencana Pembelajaran Inovative dan Evaluasi Pembelajaran di Sekolah Kejuruan Bidang Matematika - Zukhrufurrohmah Zukhrufurrohmah; Octavina Rizky Utami Putri; Mohammad Syaifuddin; Harfin Lanya; Putri Jhahrotul Fitriana (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community engagement program was conducted at SMK Muhammadiyah 1 Probolinggo to develop innovative instructional designs and assessment instruments. The method employed was qualitative-descriptive, utilizing observation note sheets, reflective note sheets, and questionnaire sheets as instruments. The program comprised three main stages: workshops, mentoring, and evaluation. The first stage involved a workshop that covered presentations on innovative learning and the development of assessment instruments. The second stage consisted of mentoring sessions for the development of innovative teaching materials and assessment instruments, conducted through one online and one offline meeting. Evaluation was carried out during the workshop using observation note sheets, mentoring sessions through reflective discussion sheets and questionnaires, and an overall assessment of the community engagement activities through questionnaires. The evaluation results indicated a 92% increase in teachers' understanding of the Merdeka Curriculum, a 77% improvement in their confidence in designing teaching modules, and a 62% increase in their comprehension of assessment types. Additionally, 77% of teachers felt capable of developing teaching modules and assessments, although challenges remained in designing appropriate evaluation instruments. Meanwhile, the use of technology in teaching increased by 54%, yet it remains an area that requires further enhancement. These findings suggest that the mentoring provided had a positive impact on teachers' competency development, particularly in designing innovative instructional strategies. Therefore, further mentoring sessions are needed with a greater focus on strengthening teachers' skills in designing assessments and integrating technology into teaching to support the optimal implementation of the Merdeka Curriculum.